2008
DOI: 10.1016/j.neuron.2008.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C-Cathepsin B Axis Regulates Amyloid Beta Levels and Associated Neuronal Deficits in an Animal Model of Alzheimer's Disease

Abstract: SUMMARY Impaired degradation of amyloid beta (Aβ) peptides could lead to Aβ accumulation, an early trigger of Alzheimer’s disease (AD). Regulation of Aβ-degrading enzymes remains largely unknown. Cystatin C (CysC, CST3) is an endogenous inhibitor of cysteine proteases, including cathepsin B (CatB), a recently discovered Aβ-degrading enzyme. The CST3 polymorphism is also associated with an increased risk of late-onset sporadic AD. Here we identified CysC as the key inhibitory mechanism of CatB-induced Aβ degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(160 citation statements)
references
References 57 publications
10
145
3
2
Order By: Relevance
“…Among the enzymes sorted by CI-MPR is CatB, a cysteine protease that degrades peptides in the endosomal-lysosomal system but also in the extracellular space following secretion (22). Because CatB specifically degrades A␤ 42 (23)(24)(25), we reasoned that the SORLA-independent effect of PACS1 knockdown on A␤ 42 levels might work by impacting the CI-MPR-CatB system. This hypothesis was supported when we detected reduced levels of CI-MPR in cell lysates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the enzymes sorted by CI-MPR is CatB, a cysteine protease that degrades peptides in the endosomal-lysosomal system but also in the extracellular space following secretion (22). Because CatB specifically degrades A␤ 42 (23)(24)(25), we reasoned that the SORLA-independent effect of PACS1 knockdown on A␤ 42 levels might work by impacting the CI-MPR-CatB system. This hypothesis was supported when we detected reduced levels of CI-MPR in cell lysates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we aimed to validate a PRM-MS assay consisting of a panel of proteins presumed to be involved in processes regarding secretory vesicle functioning, synaptic functioning, and innate immunity [12][13][14][15][16][17][18][19][20][21]. Having performed a pilot study [29], in the present study, we investigated this panel in a larger and independent cohort that included subjects with MCI in addition to patients with AD dementia and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The PRM panel consisted of neurosecretory protein VGF (VGF), chromogranin A (CHGA), and secretogranin 2 (SCG2), granins that are presumed to be involved in axonal or synaptic vesicle transport (the granins VGF, CHGA, and SCG2) [12]; cystatin C (CysC), a protease involved in Aβ degradation [13,14]; β 2 -microglobulin (β 2 M) and lysozyme C (LysC), proteins involved in the innate immune system [15,16]; and neurexins (NRXNs) NRXN-1, NRXN-2, and NRXN-3 as well as neuronal pentraxin 1 (NPTX1), neurofascin (NFASC), and neurocan core protein (NCANP), proteins involved in synapse formation and stabilization [17][18][19][20][21]. Several of these proteins, including VGF, CHGA, SCG2, CysC, and β 2 M, have been suggested in previous studies to be involved in AD pathology [12][13][14][22][23][24][25][26][27][28]. A pilot study that we performed after developing the PRM panel showed promising results, with lower levels for several proteins in patients with AD dementia compared with control subjects [29].…”
Section: Introductionmentioning
confidence: 99%
“…CysC is thus likely indirectly involved in A␤ regulation. Epidemiologically, a polymor- phism in the CysC gene (CST3) has been linked to enhanced risk for AD (66), and CysC modulates cerebral ␤-amyloidosis in A␤PP transgenic mice (71).…”
Section: Cystatin Cmentioning
confidence: 99%